On weak solutions to parabolic problem involving the fractional p-Laplacian via Young measures - Talibi, Ihya; Balaadich, Farah; Boukari, Brahim El; Ghordaf, Jalila El (Annales Mathematicae Silesianae, 2024)
In this paper, we study the local existence of weak solutions for parabolic problem involving the fractional p-Laplacian. Our technique is based on the Galerkin method combined with the theory of Young measures. In addition, an example is given to illustrate the main results.